2018
DOI: 10.3390/ijfs6010027
|View full text |Cite
|
Sign up to set email alerts
|

Gas Storage Valuation and Hedging: A Quantification of Model Risk

Abstract: This paper focuses on the valuation and hedging of gas storage facilities, using a spot-based valuation framework coupled with a financial hedging strategy implemented with futures contracts. The contributions of this paper are two-fold. Firstly, we propose a model that unifies the dynamics of the futures curve and spot price, and accounts for the main stylized facts of the US natural gas market such as seasonality and the presence of price spikes in the spot market. Secondly, we evaluate the associated model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Domestic issues and international conflicts contribute to the volatility of energy prices (Shahbaz et al, 2017). The prices of heating November impacts the oil and gas industry, disrupting off-shore activities and refineries and causing sharp seasonal spikes in crude oil and natural gas prices (Efimova and Serletis, 2014;Hénaff et al, 2018;Nick and Thoenes, 2014). The spike in the price of natural gas in 2018 provides an informative example.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Domestic issues and international conflicts contribute to the volatility of energy prices (Shahbaz et al, 2017). The prices of heating November impacts the oil and gas industry, disrupting off-shore activities and refineries and causing sharp seasonal spikes in crude oil and natural gas prices (Efimova and Serletis, 2014;Hénaff et al, 2018;Nick and Thoenes, 2014). The spike in the price of natural gas in 2018 provides an informative example.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…The SDDP method with or without conditional cuts have been implemented in StOpt [55] an open source library containing tools to solve optimization problems both in continuous or discrete time. In particular, inventory / stock problems (such as cascaded reservoir management problems, e.g., [5,47,56] or gas storage, e.g., [57,58]) can be optimized using either the Dynamic Programming method or the Stochastic Dual Dynamic Programming method. The subsequent experiments were carried out using this library.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…In addition, a comparison with low-pass filtering methods was made. The fifth paper entitled "Gas Storage Valuation and Hedging: A Quantification of Model Risk" by Hénaff et al (2018) investigates the valuation and hedging of gas storage facilities using a spot-based valuation framework coupled with a financial hedging strategy implemented with futures contracts. The authors evaluated the associated model risk, and showed that the valuation is strongly dependent on the dynamics of the spot price and the hedging strategy commonly used in the industry, leaving the storage operator with significant residual price risk.…”
Section: Papersmentioning
confidence: 99%